Paclobutrazol and phenoxaprope-P-ethyl potential as growth regulator in Carpet grass Plus® - Melero, Mariana Moreira [UNESP]; dos Santos, Patrick Luan Ferreira [UNESP]; Meira Bezerra, Jéssica Cristina [UNESP]; de Lima, Bruno Horschut [UNESP]; Pagliarini, Maximiliano Kawahata; de Castilho, Regina Maria Monteiro [UNESP] (FapUNIFESP (SciELO), 2020)
Mowing is a fundamental management for turfgrass development. However, this operation has a higher cost, requiring alternatives to mechanical handling, such as growth regulators use. Thus, the objective was to evaluate the use of paclobutrazol and phenoxa- prope-P-ethyl as growth regulators in Carpet grass Plus®. The experiment was performed in full sun, in the northwest region of São Paulo state, from January to March 2020. The grass used was planted in black plastic containers (50 x 17 cm, with a height of 15 cm, totalling 11 L of volume), previously prepared with a mixture of soil + sand (2:1). The experimental design was completely randomized, consisting of two doses of paclobutrazol (1.0 and 2.0 mL L-1) + control and two doses of phenoxaprope-P-ethyl (6.25 and 12.5 µL L-1) + control. Leaf chlorophyll index, digital image analysis and fresh leaf mass were evaluated. It was observed that for Carpet grass Plus®, there was paclobutrazol effect when used as a growth regulator, with the recommended dose of 2 ml L-1 due to its residual effect up to 35 days in reducing fresh mass, without changing the concentration of leaf chlorophyll and green colour. Phenoxaprope-P-ethyl, on the other hand, had an effect as a growth regulator for the studied species, when used in the dose of 6.25 µL L-1.
Keywords: Axonopus; embankments; fissifolius; turfgrass